Pebri Leonardo Tampubolon1* , Nuwa2 , Desy Natalia Koroh2 , Herwin Joni2 dan Yosep2: ANALISIS BIAYA PEMANFAATAN LIMBAH INDUSTRI MEBEL DI TIO ART COLLECTION KOTA PALANGKA RAYA (Cost Analysis of Utilization of Furniture Industry Waste at Tio Art Collection, Palangka Raya City) - JHT, Admin (Jurnal Hutan Tropika, 2021)
This study aims to determine the total income, production costs, absolute profit, andbreak-even point from the business of utilizing wood waste, through analysis of RevenueCost Ratio (RCR) analysis at Tio Art Collection, Palangka Raya City in 2019. Theanalysis uses a quantitative descriptive method. The results of this study indicate that thewood waste used in Tio Art Collection is ironwood waste (Eusideroxylon zwageri T et B)and balangeran wood waste (Shorea laevis Ridl.). Tio Art Collection's wood craft businessis economically viable because it has an R/C ratio of 1.73.Keywords: Wood waste, R/C ratio, cost and income.